EFEK KEBISINGAN PADA IBU RUMAH TANGGA SEKITAR BANDARA ADI SUCIPTO YOGYAKARTA - Isnawan Prahardika Nugraha; Sukismanto Sukismanto; Hendarto Budiyono (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: The increase of aircraft activities that causes the increase of noise intensity which were suffered by residents around Adi Sucipto airport, especially housewives. Objective: Aimed of  the research  to know the effect of noise on housewives living near Adi Sucipto airport Yogyakarta, in Jagalan Hamlet, Tegaltirto village, Berbah Sleman district. Method: This is a quantitative descriptive research with a cross sectional approach. This research involved by 32 housewives who live in Jagalan Hamlet, Tegaltirto village, Berbah Sleman district. Results: The results of noise measurement when a plane passing by, show as  followed: The result of Lsm (night and day) measurement at point 1 showed 50.02 dB, at point 2 showed 50.05 dB. Noise intensity of a passing airplane during 6 seconds showed between 94 dB to 100 dB. Respon of housewives showed that 32 respondents (100%) disturbed when they were communicating, 26 respondents (81.3%) suffered of stress, 6 respondents (18.8%) did not stressed. Conclusion: Thirty (93.8%) respondents experienced sleep problem, 2 respondents (6.3%) did not. The noise level caused by passing airplanes in Jagalan hamlet during 6 seconds reaches 94 dB up to 100 dB, the results of Lsm measurement at point 1 50.02 dB and point 2 showed 50.05 dB. Communication disturbance were suffered by 32 respondents, stress were suffered by 26 respondents and sleeping problem were suffered by 30 respondents.